Identification of novel stress-responsive biomarkers from gene expression datasets in tomato roots - Thompson, Andrew J.; Kevei, Zoltan (CSIRO Publishing, 2016)
Abiotic stresses such as heat, drought or salinity have been widely studied individually. Nevertheless, in the nature and in the field, plants and crops are commonly exposed to a different combination of stresses, which often result in a synergistic response mediated by the activation of several molecular pathways that cannot be inferred from the response to each individual stress. By screening microarray data obtained from different plant species and under different stresses, we identified several conserved stress-responsive genes whose expression was differentially regulated in tomato (Solanum lycopersicum L.) roots in response to one or several stresses. We validated 10 of these genes as reliable biomarkers whose expression levels are related to different signalling pathways involved in adaptive stress responses. In addition, the genes identified in this work could be used as general salt-stress biomarkers to rapidly evaluate the response of salt-tolerant cultivars and wild species for which sufficient genetic information is not yet available.
Published by CSIRO Publishing. This is the Author Accepted Manuscript. This article may be used for personal use only.
Keywords: Abiotic stress; Gene expression profiling; Stress biomarkers; Salt-stress responsive genes